Examining options for reading comprehension assessment in international contexts. (24th October 2019) - Zuilkowski, Stephanie Simmons; Piper, Benjamin; Kwayumba, Dunston; Dubeck, Margaret (Peggy)
Abstract : Background: Governments in low‐income countries and donors have invested the equivalent of hundreds of millions of dollars in enhancing reading outcomes. Although reliable measures exist to assess emergent literacy skills in international contexts, there is little consensus on the assessment of reading comprehension. Methods: Using data from 5, 389 Kenyan children attending low‐cost private schools, we compared the reading comprehension measure from the Early Grade Reading Assessment to two alternatives. We examined relationships among children's outcome scores and the degree to which children's scores on the three measures drew on the same skills. Results: Scores on the three assessments were strongly correlated, and the assessments appeared to draw on the same abilities. The patterns observed in the exploratory factor analyses held for subgroups, including fluent and nonfluent readers and across testing languages. Conclusion: The alternatives did not provide more information on reading comprehension, and we therefore recommend continued use of the Early Grade Reading Assessment standard measure. Highlights: What is already known about this topic Large‐scale reading interventions in developing countries have focused on foundational skills, such as decoding. Reliable assessments of foundational skills are available and have been used at scale in these contexts. However, the debate continues regarding how reading comprehension should be assessed, in populations with low skill levels and in contexts where tools must be straightforward and inexpensive to implement. What this paper adds We compare the standard reading comprehension measure used on the Early Grade Reading Assessment to two others. The first alternative is similar in structure but gives students more time to read the associated passage. The second alternative uses sentences rather than a passage to assess comprehension. Implications for theory, policy or practice All three measures are strongly correlated, and exploratory factor analyses suggested that they are measuring the same ability. Therefore, as the standard Early Grade Reading Assessment measure is less expensive to implement on a large scale, we see no reason to prefer one of the alternatives. However, the standard measure is not perfect, and future research should explore other options for reliably measuring assessment, particularly at very low literacy levels.